1970
DOI: 10.5812/ircmj.1600
|View full text |Cite
|
Sign up to set email alerts
|

The Supraclavicular Flap for Reconstruction of Postburn Mentosternal Contractures

Abstract: BackgroundThe thin and pliable skin of the neck is a region with multidirectional activity, and postburn scar contractures tend to form there easily. The supraclavicular flap is used to correct neck scar contractures. Its main vascular supply is the supraclavicular artery, and it can be harvested as either a skin pedicle flap or an island flap (vascular pedicle flap).ObjectiveIn this article, a total of 41 flaps are studied retrospectively and their efficacy in reconstruction of post-burn neck scar contracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…From the literature review of supraclavicular flaps for head and neck reconstruction in PubMed search engine, 26 articles [1,2,4,[11][12][13][14][15][16][17]19,20,[23][24][25][26]28,29,31,[33][34][35][36][37][38][39][40] were found that had used supraclavicular flaps for head and neck reconstruction and had clearly stated the length of flaps and their rate of necrosis ( Table 2). The rate of necrosis varied according to the size of the flaps, and only a few of the published articles clearly associated the rate of necrosis with the definite length of the flaps.…”
Section: Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature review of supraclavicular flaps for head and neck reconstruction in PubMed search engine, 26 articles [1,2,4,[11][12][13][14][15][16][17]19,20,[23][24][25][26]28,29,31,[33][34][35][36][37][38][39][40] were found that had used supraclavicular flaps for head and neck reconstruction and had clearly stated the length of flaps and their rate of necrosis ( Table 2). The rate of necrosis varied according to the size of the flaps, and only a few of the published articles clearly associated the rate of necrosis with the definite length of the flaps.…”
Section: Originalmentioning
confidence: 99%
“…In a different article, Vinh et al reported that a unilateral supraclavicular flap with an average size of 22 x 10 cm can be elevated safely [23]. Loghmani et al in a study with 41 flaps, where the range of flap size was 18 ± 6 cm in length with 3 cases of distal necrosis, had also found that the supraclavicular flap could be safely elevated, provided it was within 20 x 10 cm [36]. On the other hand, Telang et al's study found that the supraclavicular flap could be safely elevated within the dimensions of 20 × 10 cm, and the use of tissue expansion greatly amplified the total area available [37].…”
Section: Originalmentioning
confidence: 99%
“…The supraclavicular flap is a thin flap that can be pre-expanded, advanced as a tunneled flap or propeller flap. This flap provides wide coverage of the post-burn scar contractures defects in the neck and has inherited elasticity postoperatively to achieve good esthetic and functional outcomes [ 9 , 10 ]. The flap can be rotated at 130°-180° for inset into the submental and anterior neck units without cervical sagging, dog-ear, and other flap related complications [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors describe similar flaps (titled the infraclavicular flap and the anterior perforator of the transverse cervical artery flap ) but argue that the pedicle is a branch of the transverse cervical artery and not the supraclavicular artery . Pedicle dissection or skeletonization practices of high‐volume centers were variable and poorly reported, although at least three centers described dissecting proximally to increase flap reach as needed (Table ) …”
Section: Discussionmentioning
confidence: 99%
“…23,24 Pedicle dissection or skeletonization practices of high-volume centers were variable and poorly reported, although at least three centers described dissecting proximally to increase flap reach as needed (Table V). [31][32][33][34][35][36] According to this survey, surgeons performing the SCF experienced more SCF complications compared to the PMF and RFFF. One possible reason for these relatively poor outcomes may be that 53% of surgeons performing supraclavicular flaps reported being self-taught.…”
Section: Discussionmentioning
confidence: 99%